Consumer’s Perception Of Global Branding: Kopiko Product Placement In Korean Drama - Aulia Ecallypta, Saffa; Surayya Ulfa, Nurist; Qurrota Ayun, Primada (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The purpose of this study is to describe consumer perceptions of global branding using product placement strategies in Korean dramas. Qualitative research is a research method that provides descriptive data in the form of written or spoken words from individuals and the behavior of observed phenomena. The research